Análisis técnico del efecto de la inyección de polímero como método de recobro mejorado mediante simulación en el Campo Palogrande-Cebú (2019)
This degree project presents the analysis of the effect of polymerflooding as an improved recovery method in a conceptual model of the Palogrande-Cebu Field located in the Upper Magdalena Valley basin, for this was taken a laboratory injection test made in a core. From the results of the laboratory tests carried out in the core, the simulation of part of this procedure was carried out in the Computer Modeling Group program and the respective historical match of the pressure and oil production was carried out. The modeling of polymer properties such as viscosity, adsorption, concentration and residual resistance factor was carried out with an extension of the Microsoft Excel program and was provided by Ecopetrol S.A. Once the adjustment is made, the effect of the polymer on the displacement of oil is validated by changing the porous volume of polymer injected during different times. After the validation of the effect of the polymer on the simulated core, a new simulation is carried out in a conceptual model of the Palogrande-Cebu Field by polymerflooding with different properties and injection times equivalent to a “Slug Size” or porous volume of injected polymer. Finally, a sensitivity analysis of the properties or parameters of the polymer involved in the simulation of the conceptual model is carried out taking into account the increase in the recovery factor with respect to water injection.